Auctions in Do-Not-Track Compliant Internet Advertising - Reznichenko, Alexey; Guha, Saikat; Francis, Paul (Proceedings of the 18th ACM Conference on Computer and Communications Security (CCS), 2011)
Online tracking of users in support of behavioral advertising is widespread. Several researchers have proposed non-tracking online advertising systems that go well beyond the requirements of the Do-Not-Track initiative launched by the US Federal Trace Commission (FTC). The primary goal of these systems is to allow for behaviorally targeted advertising without revealing user behavior (clickstreams) or user profiles to the ad network. Although these designs purport to be practical solutions, none of them adequately consider the role of the ad auctions, which today are central to the operation of online advertising systems. This paper looks at the problem of running auctions that leverage user profiles for ad ranking while keeping the user profile private. We define the problem, broadly explore the solution space, and discuss the pros and cons of these solutions. We analyze the performance of our solutions using data from Microsoft Bing advertising auctions. We conclude that, while none of our auctions are ideal in all respects, they are adequate and practical solutions.